Platelet Counts in Uncomplicated Pregnancies at Term - Riera, Gregorio; Galindo, Megan; Turrentine, Mark (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate platelet counts at delivery in uncomplicated pregnancies between 37 and 41 weeks of gestation.Study Design Platelet counts in women 16 to 45 years of age from August 1, 2011, through May 15, 2018, with a singleton pregnancy that delivered from 370/7 to 416/7 weeks of gestation. Women with pregnancy-related complications, preexisting disorders, or on medications that could affect platelet counts were excluded.Results A total of 18,526 women had uncomplicated pregnancies with mean platelet count from 370/7 to 416/7 weeks of gestation of 220 × 109/L. The lower limit 95th percentile (2.5% quantile) was 120 × 109/L. Platelet counts decreased weekly from 37 to 41 weeks of gestation, becoming significant at 39 weeks of gestation and beyond, compared with 37 weeks (p < 0.01). Mean platelet counts: 225 × 109/L at 37 weeks, 223 × 109/L at 38 weeks, 219 × 109/L at 39 weeks, 218 × 109/L at 40 weeks, and 216 × 109/L at 41 weeks of gestation. Platelet counts of less than 150 × 109/L occurred in 9.7%.Conclusion Platelet counts in uncomplicated pregnancies decrease weekly from 37 to 41 weeks of gestation. This will be important to consider when serial platelet values are monitored for other indications.
Keywords: platelet count; pregnancy; thrombocytopenia